Curvularia Keratitis: A Fungus Among Us - Leung, Sophia (Canadian Journal of Optometry, 2024)
Purpose: This case demonstrates a less commonly encountered type of fungal keratitis caused by Curvularia species and highlights the current standard of care for fungal keratitis. Case Report: A 48 year old Caucasian female is referred with a two week history of a red, painful, and blurry right eye. Feathery borders, white focally elevated infiltrate with an overlying epithelial defect, and satellite lesions led to a clinical diagnosis of fungal keratitis. Curvurlaria was determined by culturing to be the most likely causative organism. A review of fungal keratitis and treatment strategies based on susceptibility testing and evidence-based reasoning is discussed. Conclusion: Fungal keratitis is a condition that can initially be misdiagnosed and delays in treatment can significantly affect visual outcomes. Combination of strong clinical knowledge, communication with local microbiology laboratories, and the ability to adjust treatment strategies during follow up can effectively manage this condition. Key Words: Fungal keratitis, Curvularia, voriconazole, posaconazole, culture